The Relevance of Fiscal Conditions for the Success of European Monetary Integration. (IMF Working Papers; Working Paper, 1989)
The paper argues that international differences in fiscal conditions influence the relative attractiveness of locating production facilities in different countries and could prove to be a troublesome source of instability for the European economies. Even though physical capital movements tend to occur slowly, divergent fiscal conditions can exert pressures on exchange rates in the short run, and the monetary policy reactions induced in a fixed exchange rate regime may affect real wage rates and/or employment levels. The implications for tax harmonization and budget discipline are discussed. It is argued that monetary integration itself will not induce fiscal discipline.